Function argument number identification in stripped binary under PPC and MIPS instruction set - Xiaokang YIN; Liu LIU; Long LIU; Shengli LIU (网络与信息安全学报)
The identification of the number of function argument contributes to the recovery of the function prototype and is the basis for data flow analysis and other security analysis.In order to improve the accuracy of the recognition of the number of function parameters,an algorithm (Findargs) which determines the number of parameters of the function according to the voting mechanism of the function call relationship was proposed.Findargs starts from the function call characteristics of PPC and MIPS instruction set,and uses function call relationship combined with argument pass analysis to identify the number of function arguments,which can help to recover function prototype.In order to evaluate the recognition effect of Findargs,a large binary file was selected and tested it with radare2.The experiments results show that Findargs has higher accuracy,and the accuracy rate for PPC instruction set reaches 90.3%.For MIPS instruction set,the accuracy rate is 86%.